2015
DOI: 10.3389/fpsyg.2015.01646
|View full text |Cite
|
Sign up to set email alerts
|

Non-expert listeners show decreased heart rate and increased blood pressure (fear bradycardia) in response to atonal music

Abstract: Previous studies suggested that listening to different types of music may modulate differently psychological mood and physiological responses associated with the induced emotions. In this study the effect of listening to instrumental classical vs. atonal contemporary music was examined in a group of 50 non-expert listeners. The subjects’ heart rate and diastolic and systolic blood pressure values were measured while they listened to music of different style and emotional typologies. Pieces were selected by ask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 54 publications
3
35
0
Order By: Relevance
“…It is of further interest that SCR-RR synchrony was more probable at faster tempi only in the Classical and Romantic styles, but not in the Contemporary style. We suggest, therefore, that the effect of tempo may be modulated by the context in which it occurs, supporting previous studies showing that the same features evoke different physiological responses based on the style 38,51 and/or the familiarity and engagement with the music 5 . It is worth noting that while Beethoven and Brahms were rated as more familiar compared to Dean, reported engagement did not differed across styles (see 81 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is of further interest that SCR-RR synchrony was more probable at faster tempi only in the Classical and Romantic styles, but not in the Contemporary style. We suggest, therefore, that the effect of tempo may be modulated by the context in which it occurs, supporting previous studies showing that the same features evoke different physiological responses based on the style 38,51 and/or the familiarity and engagement with the music 5 . It is worth noting that while Beethoven and Brahms were rated as more familiar compared to Dean, reported engagement did not differed across styles (see 81 ).…”
Section: Discussionsupporting
confidence: 89%
“…Timbral features, such as brighter tones and higher spectral centroid, are associated with higher arousal 32,48,49 , which correlates somewhat to SCR 35,50 . Importantly, these physiological responses are modulated by musical style: previous studies found that HR increases with faster tempo in Classical music, but decreases with faster tempo in rock music 38 , whereas HR is lower in atonal, compared to tonal music even with both styles controlled for emotion 51 .…”
Section: Introductionmentioning
confidence: 98%
“…It can be hypothesized that the lack of a quickening of RT during listening to touching music, as opposed to other stimulus types, might be due to the slower tempo (e.g., Adagio) that characterized both the tonal and atonal sad pieces with respect to the faster agitating and joyful pieces. While Bach’s melody occurs as some sort of “airy,” relaxed and lyrical dialogue between the two concertante solo violins that alternate and overlap by counterpointing each other (see Proverbio et al [ 48 ] for a complete musicological description of the pieces), in Cantus in memoriam de Benjamin Britten , the atmosphere is rarefied and suspended. Conversely, the 1st movement of Kammermusik (by Paul Hindemith, 1922, the opening passage), which was the atonal joyful piece, was characterized by Hindemith himself with the following wording: Sehrschnell und wild , translated as "very fast and wild" to refer to the agitated, repetitive and rhythmic nature of the musical writing used.…”
Section: Discussionmentioning
confidence: 99%
“…The stimuli were the same as those used in a previous psychophysiological investigation [ 22 ]. Musical pieces were selected according to the procedure described in Proverbio et al [ 48 ]. A group of 20 professional conductors, composers and professors of various Italian conservatories were asked to indicate some representative pieces that best expressed a given emotion.…”
Section: Methodsmentioning
confidence: 99%
“…The study of the deviation in the time intervals of the successive cardiac cycles is regarded as heart rate variability (HRV) [1]. Exposing an individual to stimuli like listening to music and viewing audio-visual clips has been reported to alter the ANS activity [2][3][4]. It has been well reported in the literature that HRV can be used as a non-invasive indicator of the ANS activity [5][6].…”
Section: Introductionmentioning
confidence: 99%